Republic of San Marino : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of San Marino. (IMF Staff Country Reports; Country Report ;, 2016)
This paper assesses key issues related to the economy of the Republic of San Marino. It remains in transition following the implosion of its offshore banking model in the aftermath of the global crisis, resulting in the loss of a third of output. The impact of the global financial crisis, which led to a massive outflow of nonresident deposits and a sharp downsizing of its large financial sector, caused an extraordinary loss of a third of San Marino's output-the largest in Europe. A number of important steps need to be taken for sustainable growth strengthening the banking system, realigning fiscal policy, and improving flexibility to enable the diversification.